INSTITUTIONAL SOCIAL RESPONSIBILITY IN THE INITIATIVES OF EDUCATION FOR SUSTAINABLE DEVELOPMENT IN LATVIA - Kvelde, Anna; Odina, Indra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The article deals with the implemented initiatives of education for sustainable development in educational institutions and the evidence of institutional social responsibility in them. The data were collected by the content analysis of 15 homepages of institutions implementing education for sustainable development, questionnaire to 151 students aged 14-19 years and 24 interviews with 12 principals and 12 teachers on the state of the art of sustainability issues in their organisations. The sample of 12 educational institutions, principal and teacher represented the same educational institution: 4 primary schools, 4 secondary schools and 4 state gymnasiums with a wide geographical representation – capital, urban, small town and rural schools, as well as 7 online correspondences with the representatives of organisations implementing education for sustainable development initiatives in Latvia. The data show that sustainable development initiatives are not systematically implemented and monitored in educational institutions in Latvia. There is no co-financing at national level to provide targeted methodological support for teachers in implementing practice-based education for sustainable development, instead schools attract funding from Erasmus+ or other projects. There is also a lack of a common understanding of sustainability culture among the members of the education management team, as well as no studies have been carried out on institutional social responsibility in educational institutions and regarding the implementation of education for sustainable development in curricula.